Pengaruh Tabungan Wadiah Dan Giro Wadiah Terhadap Laba Bersih Bank BRI Syariah Periode 2015-2019 - Nurul Hidayatul M; Ana Khoirun N.; Agus Eko Sujianto (Jurnal Kajian dan Penelitian Umum, 2023)
Third party money is referred to as Wadiah Savings and Wadiah Current Accounts in Islamic Banking. Banks are business-oriented organizations that prioritize profits through various strategies, including satisfying consumer needs. The purpose of this study was to determine whether Wadiah Current Accounts and Savings had an effect on Bank BRI Syariah's Net Profit from 2015 to 2019. The quantitative method used in this study included the use of secondary data and selective sampling. The information used is in the form of time series data originating from BRI Syariah Financial Statements including Wadiah Savings, Wadiah Current Accounts, and Bank BRI Syariah Net Profit from 2015 to 2019. The data in this study were examined using statistical tools with the help of the EViews program version 7.0 for windows. The results of the test using the ordinary least square method above show that the probability value of wadiah savings is 0.3702 which indicates a probability value greater than a significant value of 0.05 and the probability value of wadiah current accounts is 0.2045 which indicates a probability value greater than a significant value of 0 ,05. It was concluded that wadiah savings and wadiah current accounts had a significant influence on the profit or income of BRI Syariah bank 2015-2019